Pengembangan Kompetensi Guru Paud dalam Proses Pembelajaran Anak Usia Dini - Windi Pebriannti (Badan Penerbit STIEPARI Press, 2024)
The purpose of writing this article is to discuss the development of preschool teacher competence in the early childhood learning process. Developing the competency of Early Childhood Education (preschool) teachers is very important in improving the quality of early childhood education. Early childhood teachers must have pedagogical and professional competencies that enable them to develop innovative learning media and actualize the various potentials that children have. In several studies, it was found that there are still many preschool teachers who do not meet the competency standards set, so it is necessary to carry out training and competency development to improve the quality of education. In several community service activities, early childhood teachers are expected to be able to understand students by recognizing early childhood development and utilizing information technology as a learning medium.